Financial Globalization : Unequal Blessings - De la Torre, Augusto (World Bank, Washington, DC, 2014)
The authors present a framework to analyze financial globalization. They argue that financial globalization needs to take into account the relation between money (particularly in its role as store of value), asset and factor price flexibility, and contractual and regulatory institutions. Countries that have the "blessed trinity" (international currency, flexible exchange rate regime, and sound contractual and regulatory environment) can integrate successfully into the world financial markets. But developing countries normally display the "unblessed trinity" (weak currency, fear of floating, and weak institutional framework). The authors define and discuss two alternative avenues (a "dollar trinity" and a "peso trinity") for developing countries to safely embrace international financial integration while the blessed trinity remains beyond reach.